CULTURAL RELATIONS BETWEEN SOCIALIST STATES (ON THE EXAMPLE OF THE UZBEKISTAN SSR AND THE GDR) - Sirliboyeva Gulrukh Umar daughter (Web of Journals Publishing, 2025)
This scientific article reveals the nature of cultural relations between socialist countries using the example of the Uzbek SSR and the German Democratic Republic. Only the example of the GDR shows the general features of cultural relations in the Uzbek SSR during the Soviet period.
Keywords: Uzbek SSR, GDR, international relations, cultural relations, international culture, the idea of socialism.